3(4x-1)-7(2x+3)-(5x-9)=

Simple and best practice solution for 3(4x-1)-7(2x+3)-(5x-9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x-1)-7(2x+3)-(5x-9)= equation:


Simplifying
3(4x + -1) + -7(2x + 3) + -1(5x + -9) = 0

Reorder the terms:
3(-1 + 4x) + -7(2x + 3) + -1(5x + -9) = 0
(-1 * 3 + 4x * 3) + -7(2x + 3) + -1(5x + -9) = 0
(-3 + 12x) + -7(2x + 3) + -1(5x + -9) = 0

Reorder the terms:
-3 + 12x + -7(3 + 2x) + -1(5x + -9) = 0
-3 + 12x + (3 * -7 + 2x * -7) + -1(5x + -9) = 0
-3 + 12x + (-21 + -14x) + -1(5x + -9) = 0

Reorder the terms:
-3 + 12x + -21 + -14x + -1(-9 + 5x) = 0
-3 + 12x + -21 + -14x + (-9 * -1 + 5x * -1) = 0
-3 + 12x + -21 + -14x + (9 + -5x) = 0

Reorder the terms:
-3 + -21 + 9 + 12x + -14x + -5x = 0

Combine like terms: -3 + -21 = -24
-24 + 9 + 12x + -14x + -5x = 0

Combine like terms: -24 + 9 = -15
-15 + 12x + -14x + -5x = 0

Combine like terms: 12x + -14x = -2x
-15 + -2x + -5x = 0

Combine like terms: -2x + -5x = -7x
-15 + -7x = 0

Solving
-15 + -7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + -7x = 0 + 15

Combine like terms: -15 + 15 = 0
0 + -7x = 0 + 15
-7x = 0 + 15

Combine like terms: 0 + 15 = 15
-7x = 15

Divide each side by '-7'.
x = -2.142857143

Simplifying
x = -2.142857143

See similar equations:

| 2.5x-10=27 | | 18x=2x | | -4=(-2t+3) | | x-b=a*c | | 5x-10-X=2x+11 | | -8k+ar=r-2ysolver | | 8x-24=15 | | 12=-16t^2+24t+16 | | -8k+ar=r-2yr | | .67x-2=1.25x+.58 | | 20b-19b= | | 0=-16t^2+24t+12 | | 1/81=1/r^4 | | 3j-2j= | | 5+3(2x-4)=3+2x | | 3y+7y=22 | | g^2+3g=238 | | 3y-5x-12=0 | | 2/15=3/2(4/9x-4) | | (1/3)9×3 | | 1/3y-2=1/10y | | P^2-16pq-36q^2=0 | | 48x^2-27=0 | | 3x^2+9x+7= | | 5x+29y=-13 | | 9x^2+2x+2= | | 7x^2+3x+9= | | X^4-4x^2=21 | | X^5+7x^2=-12x | | 5(6x+1)=-25 | | g(x)=[x+2]-4 | | 2/3×1/2 |

Equations solver categories